EVALUASI HASIL PEMODELAN BATIMETRI DARI BEBERAPA KOMBINASI SATELIT ALTIMETRI PADA LAUT NATUNA DAN LAUT SULAWESI - Yustisi Ardhitasari Lumban-Gaol; Nadya Oktaviani; Prayudha Hartanto; Ibnu Sofian (Widyariset, 2020)
Indonesia is an archipelago country where 77% of its territory is waters. National marine mapping has been carried out based on depth measurement data obtained using echosounders. However, this method requires a lot of time and cost. One solution to provide Indonesian bathymetry data is by utilizing altimetry satellite data to model the bathymetry of the seafloor. This study aims to evaluate bathymetric model generated from three combinations of five altimetry satellites in shallow and deep seas. We use least square collocation gravity anomaly and geological gravity for bathymetry modeling. The results of the model show variations in deviations with sounding data available at the Geospatial Information Agency (BIG). The resulting residual trend differs between shallow and deep sea. The optimum results in shallow area is obtained by the combination of Cryosat-2, Jason-1/C, and SARAL while in deep area is obtained by the combination of ERS-1/E-F and Geosat GM. In general, the bathymetry model produced in this study has a similar profile with the sounding data.